Competing aspects in Hungarians’ household consumption: The importance of price sensitivity and environmental consciousness - Lányi, Beatrix; Jakopánecz , Eszter; Csóka, László; Neulinger, Ágnes (Vezetéstudomány / Budapest Management Review, 2024)
The Hungarian population is traditionally price-sensitive, but they are increasingly concerned about the environment. Are these aspects presented simultaneously or independently in consumer decisions related to food and household goods? How can they use price sensitivity and environmental awareness to define consumer segments? After a literature review, the authors address this question in their research project using a quantitative research methodology on a sample of consumers participating in a Hungarian retail chain’s loyalty programme. With the help of principal component and cluster analysis they can conclude that the combination of these two characteristics seems to be necessary when segmenting consumers. The authors also found that the overall group of environmentally conscious consumers includes both a price-sensitive and a price-insensitive group. This indicates the necessity to move away from a niche market approach towards a broader understanding of green consumption.